Facial Soft Tissue Thickness (FSTT) and its Sexual Dimorphism in a Malaysian Sample: A CT-Based Approach - Muhammad Faiz Mohd Fauad; Aspalilah Alias; Ker Woon Choy; Helmi Mohd Hadi Pritam; Eric Chung; Ng Wei Lin; Arofi Kurniawan; Khalid Ayidh Alqahtani; Nur Azwa Syuhada Samshuddin (Faculty of Syariah and Law, USIM, 2026)
Facial soft tissue thickness (FSTT) is a crucial element in forensic identification and facial reconstruction. Exploring its variations according to different sexes provides valuable information that is needed for an accurate identification. This study aimed to investigate FSTT variations between males and females of adult Malaysian populations. A total of 413 head and neck computed tomography (CT) scans (208 males, 205 females) of patients aged 18–65 years were selected. Four mid-sagittal landmarks; nasion, mid-philtrum, subnasale, and upper lip were involved in the measurement, using 3D-Slicer software. The effect of sex on FSTT was analysed using multivariate analysis of variance (MANOVA). MANOVA showed a statistically significant difference in FSTT between sexes (Wilks’ Lambda = 0.020, p < 0.001). All four landmarks demonstrated significant variations between males and females (all p < 0.001). Males have greater FSTT compared to females at all landmarks. In conclusion, there were significant FSTT variations between the sexes of adult Malaysian population. This population-specific data could be applied as forensic reference that tailored to Malaysian population.